Regulation of ethanol metabolism in isolated rat hepatocytes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Page, Rachel Audrey (Massey University, 1990)
The importance of an individual step in the regulation of a metabolic pathway can be quantitatively defined by determining a global coefficient called the flux control coefficient (??i). The coefficient can be evaluated by altering the pathway flux in small increments using an enzyme-specific inhibitor. This modulation approach was applied to the study of the regulation of ethanol metabolism in isolated rat hepatocytes. A procedure was developed for using isolated hepatocytes to measure the small decreases in rates of ethanol oxidation produced by increasing concentrations of inhibitor. The method, termed the two time point method, involved the incubation of replicate 1 ml or 2 ml samples in 10 ml erlenmeyer flasks containing cells, medium and substrates with varying inhibitor concentrations (including zero to provide a control rate). Using this method, the apparent flux control coefficient of ADH in hepatocytes isolated from starved rats was determined using two inhibitors, tetramethylene sulphoxide (TMSO) and isobutyrarnide (IsB). Using the initial slope of the flux inhibition curve and the appropriate inhibition constant determined for isolated ADH, the apparent cinH was calculated to be 0.37 ± 0.09 (from inhibition by TMSO) or 0.43 ± 0.10 (from inhibition by IsB). The good agreement in the value obtained for the flux control coefficient of ADH, using two different inhibitors, showed that the method developed for measuring small changes in ethanol clearance rates was providing accurate, reproducible results. These flux control coefficients were calculated on the assumption that the ADH reaction is a one substrate, one product reaction. The apparent flux control coefficient of ADH was then corrected for the concentration effect of NAD+, NADH and acetaldehyde. When substrate and product concentrations were considered, the value of the apparent cinH increased to a maximum of 0.53 (for TMSO inhibition) or 0. 63 (for IsBinhibition). These results indicate that in starved rats the activity of the enzyme alcohol dehydrogenase is one of the major factors involved in regulation of ethanol metabolism. The importance of ADH in fed rats was determined using TMSO. A range of values for the flux control coefficient of ADH was obtained with varying concentrations of acetaldehyde. The value of ??H was dependent on the concentration of acetaldehyde present in the isolated rat hepatocytes. For example the apparent flux control coefficient of ADH was about 0.02 when the acetaldehyde concentration was 138 J..LM and was approximately 0.5 when the concentration of acetaldehyde was 6 J..LM, which is analogous to conditions in starved rats. When the apparent cl.oH was corrected for the effect of substrate and product concentration the trend of decreasing cinH with increasing acetaldehyde concentration was still observed. This indicates that the importance of alcohol dehydrogenase in regulation of ethanol metabolism, in hepatocytes isolated from fed rats, decreases with increasing acetaldehyde concentration. Obviously, as the significance of ADH in regulation of ethanol oxidation decreases, other enzymes in the ethanol pathway become more important. The most likely enzyme to have an increasing importance in the regulation of ethanol elimination, with increasing concentrations of acetaldehyde, is aldehyde dehydrogenase (AIDH). Preliminary inhibitor studies were carried out on AIDH in hepatocytes isolated from starved rats, using the irreversible inhibitor disulfiram. The flux control coefficient of aldehyde dehydrogenase was calculated to be about 0.1. However, because of the problems encountered with the preparation of disulfiram stock solutions, an alternative inactivator of aldehyde dehydrogenase was required for the inhibitor titration experiments. Diethyldithiocarbamate (DDC), a metabolite of disulfiram, was used. The results showed that inhibition of AIDH occurred in the presence of DDC and that the minimum amount of DDC required for total inhibiton of aldehyde dehydrogenase was in the concentration range of 300 ??M to 500 ??· Further studies should be carried out for determination of the initial slope of the flux inhibition curve, using DDC, so that the flux control coefficient of AIDH may be calculated. In chapter 6, a theoretical approach for determining the importance of the shuttle systems and electron transport chain in regulation of ethanol oxidation in rat hepatocytes is discussed. A literature search on possible inhibitors for the malate-aspartate shuttle, a-glycerophosphate shuttle and electron transport chain was carried out. The results from this study show that it is possible to evaluate the importance of some of the individual steps in the ethanol pathway by using the modulation approach devised by Kacser and Burns. However the two time point method developed for measuring the small decreases in flux through the ethanol pathway imposed by increasing concentrations of inhibitor is only sensitive. enough to detect changes in flux as low as 8.0%. Enzymes that have low flux control coefficients will produce changes in flux of about 8.0%. Thus, the development of a more sensitive method for measuring the small changes in flux through the ethanol pathway is needed, or a method otherthan the modulation approach for calculating the flux control coefficient is required.
Keywords: Rat hepatocytes; Ethanol oxidation; Alcohol dehydrogenase; Acetaldehyde; Aldehyde dehydrogenase